CRISIS OF TRUST IN GOVERNMENT: THE ROLE OF PUBLIC RELATIONS IN ITS RESTORATION - Larysa Samoilenko; Viacheslav Sharyi; Alina Zahrebelna (Публічне управління та регіональний розвиток)
The article examines the importance of citizens' trust in state institutions in the context of modern public administration challenges. It delves into the negative consequences stemming from a lack of trust, which can significantly affect the effectiveness of management decisions, the legitimacy of political processes, and the overall stability of society. In particular, a deficiency of trust can lead to an increase in social tension, rising protest moods, and, as a consequence, the destabilization of the political situation.